2015
DOI: 10.1088/0004-637x/809/2/130
|View full text |Cite
|
Sign up to set email alerts
|

MULTI-WAVELENGTH STUDY OF FLARING ACTIVITY IN BL Lac OBJECT S5 0716+714 DURING THE 2015 OUTBURST

Abstract: We present a detailed investigation of the flaring activity observed from a BL Lac object, S5 0716+714 , during its brightest ever optical state in the second half of January 2015. Observed almost simultaneously in the optical, X-rays and γ-rays, a significant change in the degree of optical polarization (PD) and a swing in the position angle (PA) of polarization were recorded. A detection in the TeV (VHE) was also reported by the MAGIC consortium during this flaring episode. Two prominent sub-flares, peaking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 46 publications
3
52
0
Order By: Relevance
“…Furthermore, this model predicts very noisy PA swings, but observations have often seen rather smooth swings that disfavor a stochastic origin (Kiehlmann et al 2017). The third possibility is a regulated magnetic field alteration due to local energy dissipations, such as shocks or magnetic instabilities (Zhang et al 2015;Nalewajko 2017). Magnetohydrodynamic simulations have shown that shocks and kink instabilities can locally modify the magnetic field and dissipate jet energy, giving rise to correlated flares, low PD, and smoothly rotating PA.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, this model predicts very noisy PA swings, but observations have often seen rather smooth swings that disfavor a stochastic origin (Kiehlmann et al 2017). The third possibility is a regulated magnetic field alteration due to local energy dissipations, such as shocks or magnetic instabilities (Zhang et al 2015;Nalewajko 2017). Magnetohydrodynamic simulations have shown that shocks and kink instabilities can locally modify the magnetic field and dissipate jet energy, giving rise to correlated flares, low PD, and smoothly rotating PA.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to their 180 • counterparts, these events show one or multiple flares as well as low and fluctuating polarization degree (PD). But here the PA can rotate much more than 180 • , either consistently in one direction (Marscher et al 2010) or in both directions (Chandra et al 2015). Because of the large-amplitude and rather smooth PA rotation, they are unlikely due to stochastic processes in a turbulent magnetic field.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the sampling of PD is sparse, so that we cannot verify this correspondence from the two light curves directly. A better sampling example, i.e., the intra-day variation study of S5 0715+714, seems to support such correspondence, see Figure 1 in Chandra et al (2015). Based on Equation 8, the linear correlation between log and log νF ν , i.e., 2(1+α θ ) 3+αo , can be derived in the case that variations of PD and flux are due to the variation of δ, see Table 3.…”
Section: Polarization and Optical V Bandmentioning
confidence: 84%
“…The BL Lac S5 0716+714 exhibited an unprecedented optical/NIR flare on January 2015, which triggered multiwavelength observations, and detection up to VHE energies with MAGIC (Chandra et al 2015;MAGIC Collaboration, et al 2018c;Manganaro et al 2016). It is classified as an ISP (Giommi et al 1999).…”
Section: S5 0716+714mentioning
confidence: 99%